English Language Teaching with an Electronic Concept Mapping - Tezci, E.; Demirli, C.; Sapar, V. (Kassel Univ Press Gmbh, 2007)
Educational technologies have contributed greatly to the improvement of the process of education. Besides contributing to education directly, the development in new technologies made it almost compulsory to bring new approaches in teaching methods. Among these contributions can be mentioned the application of Internet Technologies in teaching. There is an ever-increasing positive impact on learning of combining technological materials with teaching methods, or using them as teaching materials. Electronic concept mapping can be considered as a teaching method to raise motivation and meaningfulness with its features being contextual, visual, multi-dimensional and interactive. Concept maps are of significant structure in language teaching because of their cognitive complexity, coherence and taxonomic organization. As concepts are contextual in English, this will create an appropriate atmosphere for it to be learnt together with its phonetic and linguistic structure. In this study a model of e-concept maps has been used as an alternative teaching method.
Keywords: Concept maps; Educational technology; English language teaching